Pancreatic cancer screening using a multiplatform human serum metabolomics system. (June 2016) - Sakai, Arata; Suzuki, Makoto; Kobayashi, Takashi; Nishiumi, Shin; Yamanaka, Kodai; Hirata, Yuichi; Nakagawa, Takashi; Azuma, Takeshi; Yoshida, Masaru
Aim: To examine a novel screening method for pancreatic cancer involving gas chromatography/mass spectrometry and liquid chromatography/mass spectrometry-based metabolomics analysis.Materials & methods: Sera from pancreatic cancer patients (n = 59) and healthy volunteers (n = 59) were allocated to the training set or validation set. Serum metabolome analysis was carried out using our multiplatform metabolomics system. A diagnostic model was constructed using a two-phase screening method that was newly advocated.Results: When the training set was used, the constructed diagnostic model exhibited high sensitivity (100%) and specificity (80%) for pancreatic cancer. When the validation set was used, the model displayed high sensitivity (84.1%) and specificity (84.1%).Conclusion: We successfully developed a diagnostic model for pancreatic cancer using a multiplatform serum metabolomics system.